Prevalencia de tuberculosis bovina (Mycobacterium spp) en fincas de la parroquia San Isidro del cantón Sucre - Ramírez Alcívar, Heidy Thairy (2024)
The objective of the study was to diagnose the prevalence of tuberculosis (Mycobacterium spp) on farms in San Isidro parish, Sucre canton using the intradermal tuberculinization technique. A non-experimental, descriptive study was carried out, where 160 female cattle from a total of 12 livestock herds in the study area were evaluated through a simple random sampling for convenience. The prevalence was determined using the tuberculin test (purified protein derivative of Mycobacterium bovis, strain AN-5) applied on the animal's neck. The results were analyzed using descriptive statistics to calculate prevalence rates and identify risk factors. No cases of Mycobacterium spp were detected in the herds of the San Isidro parish, so it was not considered necessary to perform the confirmation test after 180 days. However, potential risk factors that may favor the appearance of this infectious disease in the study area were identified, including the close interaction of cattle with humans and other domestic and wild animals, as well as the introduction of cattle from other farms and regions. The livestock farms involved in the research are currently free of the disease, which is a favorable health indicator for the herds evaluated. Nonetheless, active epidemiological surveillance should be maintained to detect any signs of bovine tuberculosis.